DEALING WITH DISTRESS IN THE TOURISM INDUSTRY: THE ROLE OF LEADERS, AGILITY AND COLLABORATION ON SME RESILIENCE - Putu Dyah Permatha Korry,; Ni Nyoman Sri Wisudawati,; I Putu Dharmawan Pradhana, (International Journal of Social Science, 2024)
Business resilience is an essential issue in entrepreneurship studies, especially in the tourism industry support sector in Bali. Dynamic and rapid changes in the industrial environment often threaten business sustainability, especially in the small and medium enterprises (SMEs) sector, the backbone of the Balinese economy. Although SMEs significantly contribute to the tourism sector, this sector remains vulnerable to change and has a relatively short business life. This study explores the factors determining business resilience in tourism-supporting SMEs by examining the relationship between entrepreneurial leadership, agility, collaboration, and resilience. This study uses a quantitative approach with Structural Equation Modeling (SEM) analysis through SMART PLS 3.0 software. Data were collected from 261 SME entrepreneurs in the creative tourism industry sector in Bali through a questionnaire. The study results indicate that entrepreneurial leadership has a direct positive effect on agility and resilience. Other findings suggest that agility directly affects collaboration and resilience, while collaboration contributes positively to resilience. In addition, the study’s results suggest an indirect effect, where agility acts as a mediating variable that strengthens the relationship between entrepreneurial leadership and resilience. At the same time, collaboration mediates the relationship between agility and resilience. This study makes an essential contribution to the Bali tourism sector by showing that entrepreneurial leadership, agility, and collaboration are key elements to increase the resilience of SMEs in facing industry dynamics. These findings provide practical insights for SME actors to strengthen business resilience through improving leadership skills, developing agility, and strategic collaboration to support the sustainability of the tourism sector in Bali